2016
DOI: 10.1007/s10620-016-4251-x
|View full text |Cite
|
Sign up to set email alerts
|

No Benefit of Oral Diclofenac on Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis

Abstract: UMIN000008109.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…With regard to route of administration, NSAIDs were administered via the rectum, IV, IM, and per OS in 12, three, one, and twp studies, respectively. The following NSAIDs were used: diclofenac 17 18 19 20 21 22 23 24 25 26 27 28 , indomethacin 11 29 30 31 32 33 34 , naproxen 35 , valdecoxib 8 , and ketoprofen 36 . Study characteristics are outlined in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to route of administration, NSAIDs were administered via the rectum, IV, IM, and per OS in 12, three, one, and twp studies, respectively. The following NSAIDs were used: diclofenac 17 18 19 20 21 22 23 24 25 26 27 28 , indomethacin 11 29 30 31 32 33 34 , naproxen 35 , valdecoxib 8 , and ketoprofen 36 . Study characteristics are outlined in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Future studies must include both intervention and control groups. In addition, diagnosis of PEP and its changes post-ERCP showed a substantial heterogeneity among the studies, which included time of evaluation after the procedure (from 90 minutes to 72 hours), clinical symptoms (pain, nausea, and vomiting), and use of imaging data (tomography) 11 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The administration route is also significant as NSAIDs administered via the rectal route effectively prevents PEP [7,9,11,12]. In contrast, the administration of NSAIDs through other routes has not been found useful [1,16,17]. There is still some controversy regarding the appropriate timing of NSAIDs administration (before/during/after ERCP).…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%
“…Many of the RCTs and the systematic analysis we reviewed in this study have shown that NSAIDs are effective in reducing the risk of PEP [ 7 , 9 - 12 ], although a few RCTs have shown that NSAIDs are not useful in PEP prevention [ 1 , 13 , 14 ]. NSAIDs provide improved prophylaxis in patients at high risk of developing PEP, as demonstrated by multiple studies [ 7 , 9 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation